Chemical composition and nutritional evaluation of transgenic cottonseed for ruminants - KUMAR, R SENTHIL; SINGHAL, K K (The Indian Journal of Animal Sciences, 2014)
Nutritional attributes of transgenic cottonseed containing Bascillus thuringiensis (Bt) protein and its commercial counterpart (Non-Bt) were estimated. Both types of cottonseed were free from fuzz and bulk density was 508 Â± 2.61 and 576 Â± 2.31 kg/m3 in Bt and non-Bt cottonseed, respectively. CP (29.48%) and EE (26.90%) contents of Bt cottonseed were higher and NDF, herni-cellulose and lignin contents were lower than in non-Bt cottonseed. Gossypol of Bt and non-Bt cottonseed (hull free basis) was 1.52 and 1.23%. a-Tocopherol and Î²-carotene, both were higher in non -Bt cottonseed (22.19 and 33.59 mg/g) than that in Bt cottonseed (11.00 and 11.62 mg/g). Amino acid composition of both types of cottonseed was comparable. Effective dry matter (EDDM) degradability of both types of cottonseed was similar (45.3%), but value for CP degradability was higher for non-Bt cottonseed (70.0%) than that in Bt cottonseed (67.1 %). Similar in sacro and in vitro DM digestibility of both types’of cottonseed indicated that Bt protein present in transgenic cottonseed did not have any adverse effect on rumen microbial population. It can be concluded that there was no difference in the nutritional value of transgenic and non -transgenic cottonseed for ruminants.